The different manifestations of 18F-FDG PET/CT and 68Ga-FAPI-04 PET/CT in evaluation of the steroid therapy response for IgG4-related disease: A case report - Jia, Guorong; Bian, Dejian; Cheng, Chao; Wang, Meitang; Zuo, Changjing (Frontiers in Nuclear Medicine, 2023)
IgG4-related disease is a fibrous-inflammatory process belonging to immunomodulation disorders. We report a case of a 57-year-old man with the IgG4-related disease (RD). 68Ga-FAPI-04 PET/CT showed more significant uptake in most lesions than in 18F-FDG PET/CT except for the cervical and mediastinal lymph nodes. Besides, uptake in the submandibular glands were only detected in 68Ga-FAPI-04 PET/CT. The biopsy result of the cervical lymph nodes confirmed the diagnosis of IgG4-related disease. After treatment, only slight FDG-avid cervical lymph nodes were observed in the 18F-FDG PET/CT, while the raised uptake of 68Ga-FAPI-04 could be observed in the pancreas and submandibular glands. 68Ga-FAPI-04 PET-CT might have promising applications in evaluating IgG4-RD, whether in initial or follow-up imaging during steroid therapy.